Covalent 2D-Engineering of Graphene by Spatially Resolved Laser Writing/Reading/Erasing - Edelthalhammer, Konstantin; Dasler, Daniela; Jurkiewicz, Lisa; Nagel, Tamara; Al-Fogra, Sabrin; Hauke, Frank; Hirsch, Andreas; Al-Fogra, Sabrin (Angewandte Chemie International Edition, 2020)
We report a facile and efficient method for the covalent 2D-patterning of monolayer graphene via laser irradiation. We utilized the photo-cleavage of dibenzoylperoxide (DBPO) and optimized the subsequent radical additions to non-activated graphene up to that level where controlled covalent 2D-patterning of graphene initiated by spatially resolved laser writing is possible. The covalent 2D-functionalization of graphene, which is monitored by scanning Raman microscopy (SRM) is completely reversible. This new concept enables write/read/erase control over the covalent chemical information stored on the graphene surface.
CRIS-Team Scopus Importer:2020-10-16
Keywords: covalent functionalization; covalent patterning; graphene; Raman spectroscopy; write/read/erase